Mechanistic Insights on the Copolymerization of Polar Vinyl Monomers with Neutral Ni(II) Catalysts - Berkefeld, Andreas; Drexler, Matthias; Möller, Heiko M; Mecking, Stefan (Journal of the American Chemical Society, 2009)
The Ni(II) complexes [(N∧O)Ni(H)(PMe3)] (1) and [(N∧O)Ni(CH2CH3)(dmso)] (3) (N∧O = κ2-{(2,6-(3,5-(F3C)2C6H3)2C6H3)−NC(H)−(3,5-I2-2-O-C6H2)}) were found to be well-defined model compounds to study the reactivity of polymerization active neutral Ni(II) species toward polar vinyl monomers. Methyl acrylate (MA) insertion into the Ni(II)−hydride bond of 1 was monitored at T ≥ −40 °C by NMR spectroscopy. 2,1-Insertion yields the functionalized Ni(II) alkyl complex [(N∧O)Ni(CαH(CH3)Cβ(O)OCH3)(PMe3)] (4). Low-temperature 2D ROESY data indicate a weak Ni(II)···OCβ interaction in 4. This is supported by ab initio calculations at the gradient-corrected DFT (BP86/LACPV*) level of theory. Exposure of 1 to equal amounts of MA and ethylene afforded 4 and the Ni(II) ethyl complex 7 in a 9:1 ratio, which indicates that MA and ethylene effectively compete with each other for coordination and insertion. NMR spectroscopic monitoring revealed that 4 is stable in the absence of residual 1 at low temperatures but is subject to rapid bimolecular elimination of the functionalized alkyl moiety in the presence of free Ni(II) hydride species even at T = −40 °C. Isomerization into the 1,2-MA-insertion product was observed at T = 25 °C but occurred slowly compared to decomposition, which occurs at 0 °C by reaction of 4 with Ni(II) hydride formed by β-elimination from 4 itself at this temperature. Exposure of the higher Ni(II) alkyl complex 3 to MA in the presence of excess ethylene results in the immediate formation of methyl pentanoate as the ultimate decomposition product. Functionalized Ni(II) alkyl species formed from 2,1-insertion of MA into the metal−carbon bond of higher Ni(II) alkyls are subject to rapid hydrolysis in the presence of trace amounts of water in the reaction medium, which contrasts the stability of nonfunctionalized Ni(II) alkyls toward water. Exposure of 1 to vinyl acetate (VA) affords the kinetic 1,2-insertion product [(N∧O)Ni(CH2CH2OCγ′(O)CH3)(PMe3)] (5) at temperatures T ≥ −10 °C, which rearranges into the thermodynamically favored 2,1-insertion product [(N∧O)Ni(CH(CH3)OC(O)CH3)(PMe3)] (6). NMR data and ab initio calculations suggest a Ni(II)···OCγ′ interaction in 6. 5 decomposes via β-acetate elimination to yield ethylene and Ni(II) acetate species. Notably, VA does not undergo observable nickel−carbon bond insertion with 3, but reacted with Ni(II) hydride species in equilibrium with 3 to yield 5* which is subject to rapid decomposition via β-acetate elimination.